Seasons and people and other songs - Kingsbury, Roy; O'Shea, Patrick ([England] : Oxford University Press, 1979)
Contains the collection of pop songs that have been written to help those who starting to learn English
APD 01063
Keywords: Popular music; English language -- Study and teaching -- Foreign speakers